Performance Limitations Due to Intra-Core Crosstalk and Nonlinear Interference Noise in Weakly Coupled Multi-Core Fiber Transmission Systems - Wencheng Li; Lian Xiang; Xiaoliu Li (Photonics)
Multi-core fiber (MCF) is expected to be a good candidate to overcome the capacity limit of single-mode single-core fiber. However, only linear inter-crosstalk was considered in the performance of MCF. In this study, the performance of the transmission channel in terms of the signal-to-noise ratio (SNR) in weakly coupled MCF transmission systems is investigated by taking into account the effect of intra-core nonlinear interference noise (NLIN) and nonlinear inter-core crosstalk (NICXT). The SNR is calculated with various MCF system parameters to assess corresponding transmission performance. The results show that the SNR cannot always be improved by increasing the transmitted power in both the SCF and MCF systems. NICXT can deteriorate the performance of the MCF system, obviously, especially when the transmitted power is smaller than the threshold power. Furthermore, this influence is more marked with a small coupling coefficient.